Toddlers' Word Learning From Contingent and Noncontingent Video on Touch Screens. Issue 2 (March 2016) - Kirkorian, Heather L.; Choi, Koeun; Pempek, Tiffany A.
Abstract : Researchers examined whether contingent experience using a touch screen increased toddlers' ability to learn a word from video. One hundred and sixteen children (24–36 months) watched an on‐screen actress label an object: (a) without interacting, (b) with instructions to touch anywhere on the screen, or (c) with instructions to touch a specific spot (location of labeled object). The youngest children learned from contingent video in the absence of reciprocal interactions with a live social partner, but only when contingent video required specific responses that emphasized important information on the screen. Conversely, this condition appeared to disrupt learning by slightly older children who were otherwise able to learn words by passively viewing noninteractive video. Results are interpreted with respect to selective attention and encoding.